Corrigendum to “A cross-sectional analysis of fall risk among institutionalized older adults in Malaysia” [Belitung Nursing Journal, 2025; 11(4): 487–495] - Zohari, Zahira; Rahim, Azliza; Mat Din, Hazwan; Saibul, Nurfaizah; Jafri, Asiah; Rahim, Shafikah; Nasir, Faizah; Sallehuddin, Hakimah (Belitung Nursing Journal, 2025)
This corrigendum corrects the author name, institutional affiliation, and participant information in the article “A cross-sectional analysis of fall risk among institutionalized older adults in Malaysia” [Belitung Nursing Journal, 2025; 11(4): 487–495, https://doi.org/10.33546/bnj.3899]. The corrections do not affect the findings or conclusions of the study.